Silver nanoparticles/montmorillonite composites prepared using nitrating reagent at water and glycerol - Valásková, Marta; Martynková, Grazyna Simha; Lesková, Jana; Capková, Pavla; Klemm, Volker; Rafaja, David (Journal of nanoscience and nanotechnology, 2008)
Three procedures (P) were applied to prepare silver nanoparticles on natural Ca-montmorillonite (MT). The intercalation of the montmorillonite with silver nitrate in aqueous solution (P1), the intercalation of the montmorillonite with silver nitrate in glycerol (P2) and the successive combination of both P1 and P2 methods resulted to P3 method. X-ray powder diffraction (XRD), high-resolution transmission electron microscopy (HRTEM) and Fourier Transform Infrared (FTIR) spectroscopy and the molecular modeling were employed to characterize silver nanoparticles and montmorillonite nanocomposite. The P1 produced MT-1 composite with 2.3 wt% Ag and the partially collapsed layered structure. Nanoparticles of silver larger than 20 nm with a lot of planar defects were randomly distributed on the MT-1 surface; nanoparticles smaller than 20 nm were oriented to the montmorillonite substrate. The MT-2 composite from P2 contained only 1 wt% of Ag. The molecular simulation model of MT-2 showed the interlayer space with the exchangeable cations and metallic silver atoms arrangement within the glycerol bilayer. The P3 produced composite MT-3 that contained 2.4 wt% Ag. The nanoparticles > 20 nm size had a well-defined geometry, very small nanoparticles were amorphous. The modeled structure showed the exchangeable cations, Ag+ and Ag0 located close to the silicate layers and monolayer of glycerol molecules in the interlayer space.